PENERAPAN MEMBACA SINTOPIKAL UNTUK MENUMBUHKAN KARAKTER DAN MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPS MELALUI PEMBELAJARAN MODEL READING GUIDE PADA SISWA KELAS IX C SMP NEGERI 16 PEKALONGAN TAHUN PELAJARAN 2012-2013 (Forum Ilmu Sosial, 2015)
The purpose of this class action research is to develop learning process skills that requires students to be independent by developing caharacter through reading activities in Social Sciences subject. Data analysis is done descriptively by comparing inter-cycles test scores. The results of this study showed an improved character correlated to the increase in student learning outcomes. 32 students of IX C class consisting of 14 boys and 18 girls experienced an increased character from the cycle I to cycle II. Research data shows an increase of 77.21% in character. In learning outcomes, there is an increase in classical mastery of 87.5% and the average of 78.26. The conclusion of this research is that the selection of learning model adapted to material characteristics and conditions of the students, with facilitation to continue syntopical reading to build characters make a maximal learning outcomes.